An Empirical Investigation on the Sustainability of Balancing Item of Balance of Payment Accounts for OIC Member Countries - Tuck , Cheong Tang; Lau, Evan (-, 2008)
This study aims to examine the sustainability of balancing item (‘net errors and omissions’) of balance of payment accounts for OIC (Organisation of the Islamic Conference) member countries. The series specific panel unit root test (SURADF unit root tests) suggest that 9 out of 23 sampled OIC member countries have their balancing item sustainable - Albania, Coted’Ivoire, Indonesia, Kuwait, Malaysia, Mozambique, Pakistan, Tunisia, and Uganda.